Alcoholism and its Effects: an Approach Based on Health Psychology - Maria de las Mercedes Pretel Olite; Belkis González Aguiar; Anabel Machado Guevara; Odalis Fernández López; Yannelys Toledo Luaces (Revista Finlay)
Alcoholism is a complex biopsychosocial disorder that requires a specialised and multidisciplinary approach focusing on both the patient and the family. Alcohol consumption is the most important addiction worldwide due to its prevalence and impact. Therefore, the main objective of a primary care physician should be to facilitate the referral of patients and their families to a structured treatment, support and guidance program during the whole detoxification process. In every health area in Cienfuegos, there are community mental health centers with a staff trained to deal with these disorders in addicts and their family. A literature review was conducted to establish the relationship between alcohol consumption and its harmful effects on health, family and society, using an approach based on Health Psychology.